DETECTION OF BACTERIAL CONTAMINANTS IN READY-TO-DRINK BEVERAGE (ZOBO) SOLD ON FEDERAL UNIVERSITY DUTSE CAMPUS, NORTHWEST NIGERIA - ADELEYE, ADENIYI OLAREWAJU; Akinterinwa, Tolulope Deborah; Amoo, Florence Kemi; Amoo, Afeez Oladeji; Asaju, Catherine Iyabo; Shiaka, Peter Gimba; Yerima, Mohammed Bello (Innovare Journal of Sciences, 2024)
Introduction: Consumption of ready-to-drink beverages is a norm in the world over. However, the presence of total coliform in any beverage renders it unfit for human consumption. Objectives: Due to non-existence of scientific data on the safety status of the ready-to-drink Zobo which is a popular local beverage, we did conduct this study to assess the bacteriological quality of the lots sold to consumers on the campus of Federal University Dutse (FUD), Nigeria. Methods: Purposive sampling was employed to sample nine (9) locally packaged Zobo in three (3) different outlets; FUD Bakery (BAK) where three (3) were assayed (BAKA, BAKB, and BAKC), FUD Backside (BS) where three (3) samples were assayed (BSA, BSB, and BSC), and Morocco Girls’ hostel (MGH) three (3) samples were assayed (MGHA, MGHB, and MGHC). Standard methods were used to assay the sampled Zobo. Results: Results obtained indicate that samples from MGH (8.0×10⁴ CFU/mL) had the lowest total viable count (TVC), while samples from BAK (2.8×10⁷ CFU/mL) recorded the highest TVC. However, samples assayed from MGH recorded no total coliform count. The number of bacterial colonies recorded in BAKA and BAKB was not significantly different from each other (p>0.05). However, the number of bacterial colonies recorded from MGHA was significantly different from those obtained in MGHB and MGHC (p<0.05). Conclusion: Due to the results obtained, we can conclude that Zobo samples assayed in the sampling points were not fit for human consumption during the conduct of our study.